Tanggung Jawab Pemasyarakatan Terhadap Hak Atas Kebebasan Beribadah Narapidana Muslim (Studi Di Lembaga Pemasyarakatan Kelas IIB Jombang) - Zakiy Bima Kusuma Aliyan (Al Hikmah, 2020)
ABSTRACTThere are local regulations regarding the rights of citizens exercise in accordance with the religious, islam is the religion of dominant country because a number of the most people .Everyone free people to run , no more getting ganguan or disrupt their nets worship no exception for an inmate .Are equal as indonesian citizens .Personality spiritual guidance in the form of islam in a correctional institution is disenchant many prisoners , make them aware of and did not want any more repeated crimes .But was running the religious right is fairly for every muslim prisoners , whether any prisoners have freedom to worship , to depart from this writers with penelitianya who uses the interpretive in data obtained from the descriptive verbal , observation and in use.Keywords : The right to freedom of worship , convicts , human rights